Democracia, transparência pública e controle cidadão um estudo de caso do Portal de Transparência de Santa Maria/RS - Riquinho, Cláudia Lazzarotto (2014)
This research investigates the importance of public transparency, conveyed in electronic portals as an effective mechanism for strengthening democracy and citizen control. This placement of public information in electronic portals is a recent practice in the Brazilian reality, much as are the recent laws created to regulate such access, which ultimately encourage a culture of citizen participation in public life. And to make sure that this transparency provides effective opportunities to citizen control a case study of the transparency portal of the City of Santa Maria, RS is done, due to the fact that it is the closest public sphere to the citizens, with the broader goal of linking public transparency and vertical accountability as redirecting practices of state action.